Ion-doped bismuth layer piezoelectric ceramic and method for preparing the same
Patent Information
- Application Number
- CN202611109605.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
然而,压电陶瓷的性能往往是相互影响的,压电系数提高的同时温度稳定性通常会降低
本发明采用低价离子Zn2+和高价离子Nb5+进行B位等价共掺杂,取代Na0.5Bi4.5Ti4O15中的Ti4+离子。根据电荷补偿原理,引入ZnO和Nb2O5后,Zn2+和Nb5+离子取代Ti4+离子,可产生NbTi·和ZnTi″缺陷,并捕获氧空位形成(ZnTi″-VO″)缺陷偶极子,从而有效降低氧空位浓度。氧空位浓度的下降一方面可以降低氧空位对畴壁的钉扎作用,使得铋层状压电陶瓷在极化过程中畴壁更容易发生翻转,有利于压电性能的提高;另一方面可以降低载流子等缺陷的浓度,从而改善电学性能。
Smart Images

Figure CN122977834A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of piezoelectric ceramic materials technology, specifically relating to an ion-doped bismuth layered piezoelectric ceramic and its preparation method. Background Technology
[0002] Piezoelectric ceramics are widely used in the electronics industry due to their unique electromechanical conversion properties. In recent years, with the rapid development of modern industries such as aerospace and nuclear energy, the demand for advanced piezoelectric materials with higher operating temperatures (>500℃) has been increasing. Currently, the most widely used piezoelectric materials are mainly perovskite structures, although these materials have a very high piezoelectric coefficient (d...). 33 However, most bismuth-based ferroelectric materials have a Curie temperature (Tc) below 500℃, which is insufficient for high-temperature applications. In contrast, bismuth-layered ferroelectric materials exhibit great potential in high-temperature applications due to their high Curie temperature (>600℃), excellent thermal stability, and significant fatigue resistance.
[0003] The structure of bismuth layered ferroelectrics consists of bismuth-oxygen layers (Bi2O2) with a fluorite-like structure. 2+ and perovskite-like layer (A m- 1B m O 3m+1 ) 2- The layers are arranged alternately along the c-axis, with A-sites consisting of 12-coordinated low-valence cations and B-sites consisting of 6-coordinated high-valence cations, where m represents the number of perovskite-like layers. However, because the spontaneous polarization of this type of material is confined to the ab-axis, the piezoelectric coefficient is relatively low. Furthermore, the Bi element is prone to volatilization at high temperatures during preparation, leading to an increase in oxygen vacancy concentration and exacerbating the negative impact of carrier and other defects on electrical properties, further limiting its practical applications.
[0004] To address the aforementioned issues, ion doping is currently a common method to enhance the piezoelectric properties of bismuth layered piezoelectric ceramics. For example, by using Ce... 4+ Ion doping can reduce Na 0.5 Bi 4.5 Ti4O 15 The piezoelectric coefficient of the ceramic was increased from 16 pC / N to 20 pC / N; through the A / B site Ca 2+ and (W) 1 / 3 Cr 2 / 3 ) 4+ Ion doping can increase its piezoelectric coefficient to 34 pC / N. However, the properties of piezoelectric ceramics are often interdependent; an increase in piezoelectric coefficient usually leads to a decrease in temperature stability. Improving the thermal stability of the piezoelectric properties while maintaining high piezoelectric performance is one of the key research focuses in bismuth layered piezoelectric ceramics. Summary of the Invention
[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. To this end, the present invention provides an ion-doped bismuth layered piezoelectric ceramic and its preparation method, which effectively improves piezoelectric performance through co-doping with equivalent ions at the B site, and enhances the pinning effect of defect dipoles on domain walls through aging treatment, thereby significantly improving the temperature stability of the piezoelectric performance.
[0006] The first aspect of the present invention provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15 , where 0.001≤x≤0.1.
[0007] The technical solution of this invention regarding ion-doped bismuth layered piezoelectric ceramics has at least the following beneficial effects: This invention uses low-valence ions Zn 2+ and high-valence ions Nb 5+ Perform B-site equivalent co-doping to replace Na 0.5 Bi 4.5 Ti4O 15 Ti in 4+ Ions. Based on the charge compensation principle, after introducing ZnO and Nb₂O₅, Zn… 2+ and Nb 5+ Ion-substituted Ti 4+ Ions can produce Nb Ti · and Zn Ti "Defects, and capture oxygen vacancy formation (Zn Ti The "-VO" defect dipole effectively reduces the oxygen vacancy concentration. This decrease in oxygen vacancy concentration reduces the pinning effect of oxygen vacancies on domain walls, making it easier for domain walls to flip during polarization in bismuth layered piezoelectric ceramics, thus improving piezoelectric performance. Furthermore, it reduces the concentration of defects such as charge carriers, thereby improving electrical performance.
[0008] Meanwhile, due to the smaller radius of Ti 4+ (0.605Å) is affected by Zn with a larger radius. 2+ (0.74Å) and Nb 2+ The replacement of (0.64Å) exacerbates the lattice distortion of oxygen octahedra in the bismuth layered structure, thereby enhancing the spontaneous polarization of bismuth layered piezoelectric ceramics and improving their piezoelectric properties.
[0009] In addition, (Zn 1 / 3 Nb 2 / 3 ) 4+Refining the domain wall size within the ceramic reduces the energy barrier for domain wall movement, thus improving piezoelectric properties. However, the refined domain walls are easily disturbed at high temperatures, leading to a decrease in piezoelectric performance. This invention further utilizes an aging treatment to refine the piezoelectric properties of low-cost Zn. 2+ (Zn) formed with oxygen vacancies Ti Under thermal activation conditions, the defective dipoles of "-VO" undergo preferential orientation, forming an internal bias field. This significantly increases the activation energy barrier for domain wall motion, enhances the pinning effect of the defective dipoles on the domain walls, and makes the polarized domain walls more difficult to change due to external disturbances, thereby improving the temperature stability of piezoelectric properties.
[0010] According to some embodiments of the present invention, in the chemical composition, 0.01 ≤ x ≤ 0.04. When x < 0.01, the charge compensation effect generated by a small amount of doping is weak and insufficient to significantly reduce the oxygen vacancy concentration. Furthermore, the low doping concentration is insufficient to significantly alter the crystal structure or generate enough defect dipoles, thus limiting the improvement in piezoelectric performance. When x > 0.04, excessive dopant ions promote ceramic grain growth, reduce the number of grain boundaries, and prevent all dopant ions from entering the crystal lattice, forming impurity phases at the grain boundaries, leading to a decrease in piezoelectric performance. Therefore, preferably, 0.01 ≤ x ≤ 0.04.
[0011] A second aspect of the present invention provides a method for preparing ion-doped bismuth layered piezoelectric ceramics, comprising the following steps: (1) Weigh the raw materials containing Na, Bi, Ti, Zn and Nb according to the stoichiometric ratio, ball mill them together, dry them and sieve them to obtain mixed powder, and pre-calcine the mixed powder to obtain pre-calcine powder; (2) A portion of the pre-fired powder is granulated, tableted, and cold isostatically pressed to obtain a green body; (3) Perform glue removal treatment on the blank; (4) The pre-fired powder is used to embed the debinding green body, and then sintered to obtain ceramic sheets; (5) The ceramic sheet is ground and polished, electrodes are printed, and high-temperature curing is performed. The cured ceramic sheet is then subjected to polarization treatment. (6) The polarized ceramic sheet is subjected to aging treatment to obtain the ion-doped bismuth layered piezoelectric ceramic.
[0012] The technical solution of the preparation method of this invention has at least the following beneficial effects: The preparation method of this invention employs a traditional solid-state sintering method, requiring no expensive equipment or complex process control. Raw materials are readily available, production costs are low, and it is easy to industrialize. The pre-firing process effectively removes impurities from the powder while simultaneously synthesizing the desired crystalline phase. The pre-firing powder is also used for embedded powder sintering, with a single-layer covering method and a thickness close to that of the ceramic green body, approximately 1 mm. This effectively reduces Bi volatilization during sintering and prevents ceramic sheets from sticking together. The segmented heating sintering method helps improve the quality of the sintered sheets and reduces thermal stress.
[0013] According to some embodiments of the present invention, the ball milling mixing in step (1) is wet ball milling, and the ball milling speed is 300 rpm. 500 r / min.
[0014] According to some embodiments of the present invention, the ball milling time in step (1) is 4 hours. 12h.
[0015] According to some embodiments of the present invention, the drying temperature in step (1) is 80°C. 90℃.
[0016] According to some embodiments of the present invention, the drying time in step (1) is 1 minute. 2h.
[0017] Optimal ball milling conditions facilitate thorough and uniform mixing of raw materials, ensuring the uniformity of subsequent reactions.
[0018] According to some embodiments of the present invention, the pre-firing temperature in step (1) is 750°C. 850℃.
[0019] According to some embodiments of the present invention, the pre-firing time in step (1) is 2 seconds. 4h.
[0020] Preferably, the pre-calcination conditions are 800°C for 3 hours. Pre-calcination allows the chemical reactions between the raw materials to proceed fully, synthesizing the desired phase, while also removing impurities from the raw materials and increasing density.
[0021] According to some embodiments of the present invention, the pressure of the tablet compression in step (2) is 5. 10MPa.
[0022] According to some embodiments of the present invention, the holding time of the tablet in step (2) is 10 minutes. 60s.
[0023] According to some embodiments of the present invention, the pressure of the cold isostatic pressing process in step (2) is 200 MPa.
[0024] According to some embodiments of the present invention, the holding time of the cold isostatic pressing process in step (2) is 10 minutes. 30 minutes.
[0025] Granulation and tableting can effectively improve sample density and reduce porosity, thereby improving sample quality; cold isostatic pressing can further improve the density and uniformity of the preform.
[0026] According to some embodiments of the present invention, the debinding process in step (3) is as follows: holding at 350°C for 1 hour, then raising the temperature to 500°C and holding for 1 hour, with a heating rate of 1°C / min. The debinding process is used to remove the binder (such as polyvinyl butyral PVB) added during granulation, so as to avoid cracking of the green body caused by the volatilization of the binder during sintering.
[0027] According to some embodiments of the present invention, the sintering in step (4) is carried out by a segmented heating method: first, the temperature is increased to 850°C at a rate of 3°C / min. 950℃, then increase the temperature to 1020℃ at a rate of 2℃ / min. 1100℃, heat preservation 1 3 hours. Segmented heating helps improve the quality of the fired sheets, reduce thermal stress, and prevent ceramic sheets from deforming or cracking.
[0028] According to some embodiments of the present invention, the polarization treatment conditions in step (5) are: polarization temperature 160°C. 200℃, heating rate 3 5℃ / min, polarization electric field 10 16kV / mm, pressurization rate 10V / s, polarization time 20 After 40 minutes of polarization, the ceramic is allowed to cool naturally in an oil bath. Optimal polarization conditions allow for the full orientation of the electric domains within the ceramic, resulting in optimal piezoelectric properties.
[0029] According to some embodiments of the present invention, the aging treatment temperature in step (6) is 450°C. 550℃.
[0030] According to some embodiments of the present invention, the aging treatment time in step (6) is 1 hour. 5 days.
[0031] The aging process causes defective dipoles to undergo preferential orientation under thermal activation conditions, forming an internal bias field, which significantly improves the temperature stability of piezoelectric properties.
[0032] A third aspect of the present invention provides the application of the above-described ion-doped bismuth layered piezoelectric ceramics in high-temperature piezoelectric devices.
[0033] The technical solution of this invention regarding applications has at least the following beneficial effects: The piezoelectric ceramic provided by this invention has a high piezoelectric coefficient and excellent temperature stability in the range of room temperature to 500°C, and is suitable for piezoelectric sensors, transducers, drivers and other devices in high-temperature environments such as aerospace, nuclear energy, and automotive electronics. Attached Figure Description
[0034] Figure 1 Na with different doping levels x 0.5 Bi 4.5 Ti 4-x (Zn1 / 3Nb2 / 3) x O 15 High-temperature in-situ piezoelectric coefficient curve of ceramics.
[0035] Figure 2 The curves show the comparison of the high-temperature in-situ piezoelectric coefficients of NBTZN-1 ceramic (x=0.01) before and after aging.
[0036] Figure 3 This invention differs from other Na technologies in the prior art. 0.5 Bi 4.5 Ti4O 15 A comparison of the piezoelectric properties and Curie temperature of the base ceramic.
[0037] Figure 4 The curves show the comparison of the high-temperature in-situ piezoelectric coefficients of undoped NBT ceramics before and after aging.
[0038] Figure 5 This is a picture of an actual NBTZN-1 ceramic.
[0039] Figure 6 Na with different doping levels x 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15 XRD pattern of ceramics. Detailed Implementation
[0040] The following are specific embodiments of the present invention, and the technical solutions of the present invention will be further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0041] In a first aspect, some embodiments of the present invention provide an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15, where 0.001≤x≤0.1.
[0042] In conjunction with the first aspect, in some embodiments of the present invention, 0.01 ≤ x ≤ 0.04. Within this preferred range, the B site (Zn) 1 / 3 Nb 2 / 3 ) 4+ Ion doping can effectively reduce oxygen vacancy concentration and enhance lattice distortion, without causing impurity phase formation and piezoelectric performance degradation due to excessive doping.
[0043] In conjunction with the first aspect, in some embodiments of the present invention, the piezoelectric ceramic undergoes an aging treatment at a temperature of 450°C. 550℃, for 1 hour Five days. The aging treatment causes defective dipoles to undergo preferred orientation under thermal activation conditions, forming an internal bias field, which significantly improves the temperature stability of piezoelectric properties. Experiments show that the in-situ piezoelectric coefficient of NBTZN-1 ceramics at 500℃ decreased by only 9.6% after aging treatment, compared to 23% before aging.
[0044] In a second aspect, some embodiments of the present invention provide a method for preparing ion-doped bismuth layered piezoelectric ceramics, the specific steps of which are as follows: (1) According to the stoichiometric ratio Na 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15 Weigh out powders of Na2CO3 (99.8%), Bi2CO3 (99.9%), TiO2 (99%), ZnO (99.99%), and Nb2O5 (99.99%). (2) Pour the prepared raw materials into a polytetrafluoroethylene ball mill jar, add zirconia grinding balls, the mass ratio of raw materials to grinding balls is 1:4.5, and the mass ratio of large, medium and small grinding balls is 4:3:3. Add an appropriate amount of anhydrous ethanol for wet ball milling, and the ball milling speed is 300 rpm. 500 r / min, ball milling time 4 12h; the ball-milled slurry at 80 Dry at 90℃ for 1 minute 2 hours, pass through a 60-mesh sieve; (3) Pour the powder into an alumina crucible for pre-firing at a temperature of 750°C. 850℃, preheating time 2 4h; preferably, the pre-firing conditions are 800℃ for 3h. (4) Granulation is performed using the pre-calcined powder, with the binder being an alcohol solution containing 6 wt% polyvinyl butyral (PVB), and 4% of the pre-calcined powder weight is added. Prepare a 6% PVB solution and grind thoroughly until the alcohol evaporates. Pass the granulated powder through a 60-mesh sieve. Weigh 0.35g of the granulated powder each time and pour it into a 10mm diameter circular tableting mold. Press the mold at 5°C. Holding pressure at 10MPa for 10 Press molding for 60 seconds; then cold isostatic pressing at 200 MPa for 10 seconds. 30 minutes; (5) Perform glue removal treatment on the blank: keep it at 350℃ for 1 hour, then raise the temperature to 500℃ and keep it at 1 hour, with a heating rate of 1℃ / min; (6) The sample after debinding is embedded with pre-fired powder. The embedding method is a single layer of coverage with a powder thickness of about 1 mm. Then, solid-state sintering is performed at a sintering temperature of 1020 °C. 1100℃, heat preservation time 1 3 hours; using a segmented heating method: heating at 3℃ / min to 850℃ After reaching 950℃, the temperature is increased to the sintering temperature at a rate of 2℃ / min. (7) Polish the sintered ceramic disc, print a high-temperature silver paste with a thickness of about 0.01 mm on both sides, and cure it at 720℃ for 15 min. (8) The sample was polarized by oil bath heating at a polarization temperature of 160°C. 200℃, heating rate 3 5℃ / min, polarization electric field 10 16kV / mm, pressurization rate 10V / s, polarization time 20 40 min, followed by natural cooling in the oil bath after polarization; (9) Place the polarized ceramic sheet at 450°C. Aging treatment at 550℃ in air environment 1 5 days.
[0045] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0046] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0047] Unless otherwise specified, "room temperature" in this invention means 25℃±5℃.
[0048] Unless otherwise specified, "about" in this invention means that the allowable error is within ±2%.
[0049] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0050] In the embodiments, the room temperature piezoelectric properties are determined by the quasi-static d 33 The measurements were performed using a measuring instrument (ZJ-60BN, Institute of Acoustics, Chinese Academy of Sciences); high-temperature in-situ piezoelectric properties were tested using a high-temperature piezoelectric analyzer (PTS1000, Wuhan Bailibo Technology Co., Ltd.); dielectric properties were measured using an LCR analyzer (E4990A, Keysight) at a frequency of 1MHz, with a temperature range from room temperature to 700℃; DC resistivity was measured using a high resistance meter (6517B, Keithley). The heating rate used in all the above tests was 3℃ / min.
[0051] Example 1 This embodiment provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 3.99 (Zn 1 / 3Nb 2 / 3 ) 0.01 O 15 (That is, x=0.01, denoted as NBTZN-1).
[0052] The preparation method is as follows: (1) According to the stoichiometric ratio Na 0.5 Bi 4.5 Ti 3.99 (Zn 1 / 3 Nb 2 / 3 ) 0.01 O 15Weigh out powders of Na2CO3 (99.8%), Bi2CO3 (99.9%), TiO2 (99%), ZnO (99.99%), and Nb2O5 (99.99%). (2) Pour the prepared raw materials into a polytetrafluoroethylene ball mill jar, add zirconia grinding balls, the mass ratio of raw materials to grinding balls is 1:4.5, and the grinding balls of three sizes, large, medium and small, are in a mass ratio of 4:3:3. Add an appropriate amount of anhydrous ethanol for wet ball milling, the ball milling speed is 400 r / min, and the ball milling time is 8h. Dry the ball milled slurry at 85℃ for 1h and pass it through a 60 mesh sieve. (3) Pour the powder into an alumina crucible for pre-firing at a temperature of 800°C for 3 hours; (4) Granulation is carried out using the pre-calcined powder. The binder is an alcohol solution containing 6 wt% polyvinyl butyral (PVB). 5% of the weight of the pre-calcined powder PVB solution is added and ground thoroughly until the alcohol evaporates. The powder is then passed through a 60-mesh sieve. 0.35 g of the granulated powder is weighed each time and poured into a circular tablet mold with a diameter of 10 mm. The mold is then pressed at 8 MPa for 30 s. Cold isostatic pressing is then performed at a pressure of 200 MPa for 20 min. (5) Perform glue removal treatment on the blank: keep it at 350℃ for 1 hour, then raise the temperature to 500℃ and keep it at 1 hour, with a heating rate of 1℃ / min; (6) The sample after debinding was embedded with pre-burned powder. The embedding method was a single layer of coverage with a thickness of about 1 mm. Then solid-state sintering was carried out at a sintering temperature of 1050℃ and a holding time of 2h. The segmented heating method was adopted: the temperature was increased to 900℃ at 3℃ / min, and then increased to sintering temperature of 1060℃ at 2℃ / min and held for 2h. (7) Polish the sintered ceramic disc, print a high-temperature silver paste with a thickness of about 0.01 mm on both sides, and cure it at 720℃ for 15 min. (8) The sample was polarized by heating in an oil bath at a polarization temperature of 180℃, a heating rate of 4℃ / min, a polarization electric field of 14kV / mm, a pressure rate of 10V / s, and a polarization time of 30min. After polarization, the oil bath was allowed to cool naturally. (9) The polarized ceramic sheet was placed in an air environment at 500℃ for 3 days for aging treatment.
[0053] The piezoelectric coefficient d of the NBTZN-1 ceramic obtained in this embodiment was tested. 33 It has a strength of 32.1 pC / N, a Curie temperature of 650℃, and a resistivity of 0.98 × 10⁻⁶ at 500℃. 7 Ω·cm. After aging treatment, the piezoelectric coefficient d of this ceramic... 33It remains at a high value of 30.9 pC / N, and the percentage decrease in in-situ piezoelectric coefficient at 500°C has improved from 23% before aging to only 9.6%.
[0054] Example 2 This embodiment provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 3.98 (Zn 1 / 3Nb 2 / 3 ) 0.02 O 15 (i.e., x = 0.02).
[0055] The preparation method is basically the same as in Example 1, except that x = 0.02. The piezoelectric coefficient d of the ceramic obtained in this example was tested. 33 The ratio is 29.2 pC / N, and the Curie temperature is 648℃.
[0056] Example 3 This embodiment provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 3.97 (Zn 1 / 3Nb 2 / 3 ) 0.03 O 15 (i.e., x = 0.03).
[0057] The preparation method is basically the same as in Example 1, except that x = 0.03. The piezoelectric coefficient d of the ceramic obtained in this example was tested. 33 The value is 28.4 pC / N, and the Curie temperature is 650℃.
[0058] Example 4 This embodiment provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 3.96 (Zn 1 / 3Nb 2 / 3 ) 0.04 O 15 (i.e., x = 0.04).
[0059] The preparation method is basically the same as in Example 1, except that x = 0.04. The piezoelectric coefficient d of the ceramic obtained in this example was tested. 33 The ratio is 26.3 pC / N, and the Curie temperature is 650℃.
[0060] Example 5 This embodiment provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na.0.5 Bi 4.5 Ti 3.999 (Zn 1 / 3Nb 2 / 3 ) 0.001 O 15 (i.e., x = 0.001).
[0061] The preparation method is basically the same as in Example 1, except that x = 0.001. The piezoelectric coefficient d of the ceramic obtained in this example was tested. 33 It is approximately 18.5 pC / N.
[0062] Example 6 This embodiment provides an ion-doped bismuth layered piezoelectric ceramic with a chemical composition of Na. 0.5 Bi 4.5 Ti 3.9 (Zn 1 / 3Nb 2 / 3 ) 0.1 O 15 (i.e., x=0.1).
[0063] The preparation method is basically the same as in Example 1, except that x = 0.1. The piezoelectric coefficient d of the ceramic obtained in this example was tested. 33 It is approximately 22.1 pC / N.
[0064] Comparative Example 1 This comparative example provides undoped NBT ceramics (x=0), prepared using a method essentially the same as in Example 1, except that (Zn) is not used. 1 / 3 Nb 2 / 3 ) 4+ Doping. Testing showed that the piezoelectric coefficient d of pure NBT ceramics... 33 It is 17.2 pC / N.
[0065] Comparative Example 2 This comparative example provides a sample of NBTZN-1 ceramic without aging treatment. The preparation method is basically the same as in Example 1, but no aging treatment is performed after polarization. Testing showed that the in-situ piezoelectric coefficient of this sample decreased by 23% at 500°C, which is significantly higher than the 9.6% decrease of the aged sample.
[0066] Comparative Example 3 This comparative example provides an aged NBT ceramic sample. The preparation method is basically the same as that of Comparative Example 1, but after polarization, it is subjected to the same aging treatment as in Example 1 (500°C, 3 days). Testing revealed that the high concentration of oxygen vacancies inside the sample was thermally activated after the high-temperature aging treatment, resulting in increased fluctuations in piezoelectric properties at high temperatures. This indicates that the effects described in this invention cannot be obtained by directly performing aging treatment without doping.
[0067] The performance parameters of NBTZN-100x ceramics with different doping amounts x are shown in Table 1.
[0068] Table 1 Different doping amounts x NBTZN-100 x Some important performance parameters of ceramics
[0069] The samples in Table 1 are data from samples that have not undergone aging.
[0070] Furthermore, a comparison of the present invention with other works is shown in Table 2.
[0071] Table 2
[0072] Performance testing Figure 1 The high-temperature in-situ piezoelectric coefficient curves of NBTZN-100x ceramics with different doping concentrations x are shown in the figure. It can be seen from the figure that the piezoelectric coefficients of all samples decrease to varying degrees with increasing temperature, indicating that (Zn...) 1 / 3 Nb 2 / 3 ) 4+ After doping leads to refinement of domain walls, the fine domains are easily disturbed under high temperature, resulting in a decrease in the temperature stability of piezoelectric properties.
[0073] Figure 2 The figure shows a comparison curve of the in-situ piezoelectric coefficient of NBTZN-1 ceramic before and after aging. As can be seen from the figure, after aging treatment, the decrease in the in-situ piezoelectric coefficient of NBTZN-1 ceramic at 500℃ improved from 23% before aging to only 9.6%, indicating that aging treatment significantly improved the temperature stability of piezoelectric properties.
[0074] Figure 3 This invention differs from other Na technologies in the prior art. 0.5 Bi 4.5 Ti4O 15 A comparison of the piezoelectric properties and Curie temperature of the base ceramic. As can be seen from the figure, while other works improve the piezoelectric properties, the Curie temperature decreases to some extent (below 650℃ for pure NBT), while the NBTZN-1 sample in this invention maintains an excellent Curie temperature (650℃) while achieving excellent piezoelectric properties (32.1 pC / N).
[0075] Figure 4The figure shows a comparison of the high-temperature in-situ piezoelectric coefficients of undoped NBT ceramics before and after aging. As can be seen from the figure, the in-situ piezoelectric properties of the ceramics aged directly without doping become more unstable, indicating that simple aging treatment cannot achieve the technical effects of this invention.
[0076] Figure 5 This is a photo of an actual NBTZN-1 ceramic product.
[0077] Figure 6 The XRD patterns of NBTZN-100x ceramics with different doping concentrations x are shown in the figure. As can be seen from the figure, under the preferred composition of this invention (0.01 ≤ x ≤ 0.04), the XRD patterns of all ceramic samples correspond to the standard NBT card, and no impurity phases are observed, indicating that (Zn) 1 / 3 Nb 2 / 3 ) 4+ The ions have successfully entered the crystal lattice.
[0078] It should be noted that this invention proposes a strategy of modifying the substrate by introducing an aging process based on equivalent doping at the B site. In this case, B-site ion doping replaces Na. 0.5 Bi 4.5 Ti4O 15 Zinc and niobium elements were used for doping, with the B-site equivalent dopant ion combination being (Zn... 1 / 3 Nb 2 / 3 ) 4+ That is, the composition is Na 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15 In particular, this strategy can effectively reduce oxygen vacancy concentration, enhance lattice distortion, and refine domain wall size, thereby improving piezoelectric performance, which is within the scope of this patent.
[0079] By using high-temperature aging treatment, the pinning effect of defect dipoles formed by the introduced low-valence ions on domain walls is enhanced, thereby improving the temperature stability of piezoelectric properties, which is within the scope of protection of this invention.
[0080] Pre-calcined powder is used for granulation and tableting. Pre-calcination effectively removes impurities from the powder and generates NBT powder. Furthermore, the pre-calcined powder is used for embedded powder sintering to reduce Bi volatilization during sintering and prevent ceramic sheets from sticking together. Samples are then prepared using solid-state sintering, with staged heating to improve the sintering quality. For this experimental scheme, the preferred sintering process is 1060℃ for 2 hours, with a heating / cooling rate of 2-3℃ / min. The temperature is first raised to 900℃ at 3℃ / min, and then raised to the sintering temperature at 2℃ / min, which is within the scope of this patent protection.
[0081] Based on the experimental results, through the B site (Zn) 1 / 3 Nb 2 / 3 ) 4+ Ion doping significantly enhances the piezoelectric properties of ceramics. After aging treatment, the rate of change in piezoelectric properties remains within 10% in the temperature range from room temperature to 500℃, exhibiting excellent temperature stability. Therefore, the strategy of using B-site equivalent doping synergistic aging treatment can effectively improve piezoelectric properties while achieving high temperature stability of piezoelectric properties at high temperatures.
[0082] It is understandable that the high- and low-valence cations at the B site are used to replace Ti through composite doping. 4+ From the perspective of Na 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15 Zn 2+ 、Nb 5+ The element can be replaced with Ti 4+ A combination of high and low valence metal cations with similar radii, such as Ta. 5+ Sb 5+ High-valence cations and Mn 3+ Cu 2+ Combinations of low-valence cations.
[0083] In summary, this invention utilizes the B-site (Zn) 1 / 3 Nb 2 / 3 ) 4+ Equivalent doping effectively improves the piezoelectric properties of NBT ceramics. On this basis, aging treatment enhances the pinning effect of defect dipoles on domain walls, significantly improving the temperature stability of piezoelectric properties and providing new ideas and directions for the modification of bismuth layered piezoelectric ceramics.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An ion-doped bismuth layered piezoelectric ceramic, characterized in that, The chemical composition of the piezoelectric ceramic is: Na 0.5 Bi 4.5 Ti 4-x (Zn 1 / 3 Nb 2 / 3 ) x O 15 , where 0.001≤x≤0.
1.
2. The ion-doped bismuth layered piezoelectric ceramic according to claim 1, characterized in that, In the chemical composition, 0.01 ≤ x ≤ 0.
04.
3. The ion-doped bismuth layered piezoelectric ceramic according to claim 1, characterized in that, In the piezoelectric ceramic, Zn element is used in the form of Zn 2+ The Nb element exists in the form of Nb. 5+ Form exists, (Zn) 1 / 3 Nb 2 / 3 ) 4+ Ion-pair substituted Ti 4+ Bit.
4. A method for preparing ion-doped bismuth layered piezoelectric ceramics as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Weigh the raw materials containing Na, Bi, Ti, Zn and Nb according to the stoichiometric ratio, ball mill them together, dry them and sieve them to obtain mixed powder, and pre-calcine the mixed powder to obtain pre-calcine powder; (2) A portion of the pre-fired powder is granulated, tableted, and cold isostatically pressed to obtain a green body; (3) Perform glue removal treatment on the blank; (4) The pre-fired powder is used to embed the debinding green body, and then sintered to obtain ceramic sheets; (5) The ceramic sheet is ground and polished, electrodes are printed, and high-temperature curing is performed. The cured ceramic sheet is then subjected to polarization treatment. (6) The polarized ceramic sheet is subjected to aging treatment to obtain the ion-doped bismuth layered piezoelectric ceramic.
5. The method according to claim 4, characterized in that, The ball milling mixing in step (1) is wet ball milling, with a ball milling speed of 300-500 r / min and a ball milling time of 4-12 h; and / or, the drying temperature in step (1) is 80-90℃ and the drying time is 1-2 h.
6. The method according to claim 4, characterized in that, The pre-firing temperature in step (1) is 750-850℃; and / or the pre-firing time in step (1) is 2-4h.
7. The method according to claim 4, characterized in that, The pressure of the tablet in step (2) is 5-10 MPa; and / or the holding time of the tablet in step (2) is 10-60 s; the pressure of the cold isostatic pressing is 200 MPa and the holding time is 10-30 min.
8. The method according to claim 4, characterized in that, The sintering process described in step (4) is carried out in a segmented heating manner: first, the temperature is increased to 850-950℃ at 3℃ / min, and then increased to 1020-1100℃ at 2℃ / min, and held for 1-3 hours.
9. The method according to claim 4, characterized in that, The polarization conditions in step (5) are: polarization temperature 160-200℃, polarization electric field 10-16kV / mm, and polarization time 20-40min.
10. The method according to claim 4, characterized in that, The aging treatment in step (6) is performed at a temperature of 450-550℃ for 1-5 days.